Dangerous Thresholds Managing Escalation in the 21st Century - Morgan, Forrest E. (RAND Corporation, 2008)
Escalation is a natural tendency in any form of human competition, and today's security environment demands that the United States be prepared for a host of escalatory threats. This analysis of escalation dynamics and approaches to escalation management draws on a range of historical examples from World War I to the struggle against global Jihad to inform escalation-related decisionmaking.